RISK ANALYSIS OF SINGLE STOCKS AND PORTFOLIOS IN LQ45 INDEX - Astuti, Tri Heni; Pramuditha Dwi Anggraini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to measure and compare the Value at Risk (VaR) between single stocks and a portfolio within the LQ45 index using the Variance-Covariance method. Method: Daily closing prices of three companies—PT Bank Rakyat Indonesia (BBRI), PT Bank Central Asia (BBCA), and PT Astra International (ASII)—from January to October 2024 were analyzed. The Kolmogorov-Smirnov test confirmed the normal distribution of returns, validating the use of the Variance-Covariance approach. Risk for individual stocks was calculated using standard deviation, while portfolio risk incorporated covariance between asset returns. Results: The results show VaR values of Rp3,057,807 (BBRI), Rp2,243,478 (BBCA), and Rp2,928,485 (ASII) for single stocks, while the combined portfolio had a lower VaR of Rp1,985,061. Novelty: These findings indicate that diversification effectively reduces investment risk. The study provides practical insights for investors aiming to manage potential losses through portfolio construction.